2017
DOI: 10.1177/1350650117724053
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental tribological experiments and antifriction design of novel superconducting tilting pad bearing for liquid rocket engine

Abstract: Novel superconducting tilting pad bearing can realize the compound of superconducting magnetic force and hydrodynamic fluid-film force in liquid rocket engine and possesses the advantages of larger bearing capacity and higher stiffness. The indispensable small operational clearance for the bearing would possibly cause rubbing phenomena between superconducting stator and magnet rotor under impact loads. Three Y1.8Ba2.4Cu3.4Ox bulk superconductors with different crystal domains are used to study the dry friction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…In this zone, the wear and the mechanical stresses are the most important process due to the edge effects of the thrust. 6,12,2731 The second zone corresponding to the inside of the print where the wear depth has a low thickness.…”
Section: Tribological Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this zone, the wear and the mechanical stresses are the most important process due to the edge effects of the thrust. 6,12,2731 The second zone corresponding to the inside of the print where the wear depth has a low thickness.…”
Section: Tribological Resultsmentioning
confidence: 99%
“…In this zone, the wear and the mechanical stresses are the most important process due to the edge effects of the thrust. 6,12,2731…”
Section: Tribological Resultsmentioning
confidence: 99%
“…With the development of the unit towards high speed and high power density, the optimization of the performance of the tiltable pad bearing has reached the limit of the material, and the improvement of the bearing shell material has become one of the main directions of research in recent years [21][22] . Improvement of bearing performance by surface modification, such as by covering the surface of modified superconducting tiltable tile block with a thin layer of impregnated graphite, while replacing the nickel coating of the magnet with chromium plating, the results show that this friction reduction design method has improved the safety of liquid rocket motors [23] .Podrabinnik P et al [24] studied experimentally that the friction of Al-Sn-Pb-Si-Cu-Mg -Zn aluminum alloy in friction with steel and conducted experiments on journal-bearing friction pair.Madej M et al [25] investigated the effect of chemical composition of two tin-based bearing alloys (B89 and B83) on their tribological properties, and the results showed that in B83 alloy, the precipitation of the SnSb phase is the main reason for the wear resistance of the bearing alloys.Mosleh AO et al [26] developed alloys with excellent tribological properties and high mechanical properties suitable for engine bearings, and the properties of the new alloys were accurately predicted by tests with a low level of error. The application of the new materials improved the performance of the bearings, especially the limit values for stable operation at high temperatures.…”
Section: Introductionmentioning
confidence: 98%